2015 External Sector Report. (Policy Papers; Policy Paper, 2015)
After narrowing modestly in 2013, the global scale of current account imbalances, and of excess imbalances, held steady in 2014. Over the last several years, while the country composition of imbalances has rotated somewhat, overall there has been little progress on reducing excess imbalances. Excess deficits narrowed in some cases, but widened in others; progress on reducing excess surpluses has stalled. An unfinished policy agenda to reduce excess imbalances remains. Efforts by both surplus and deficit economies would be mutually reinforcing and support growth. Several significant recent developments will affect external positions in 2015: sharply lower oil prices, cyclical divergence and different monetary policies among the major economies, and related currency movements. Those developments do not overturn the previous pattern of excess imbalances and associated policy agenda, but they will have significant effects and raise new issues.